Computational analysis and experimental verification of donor–acceptor behaviour of berberine, and its co-oligomers and co-polymers with ethylenedıoxythıophene - R. M. Gamini Rajapakse; Benjamin R. Horrocks; H. M. N. P. Gunarathna; A. U. Malikaramage; M. G. S. A. M. E. W. D. D. K. Egodawele; W. H. M. R. N. K. Herath; Lahiru Sandakelum; V. M. Y. S. U. Bandara; W. V. N. S. Bowatta; J. M. Susanthi Jayasinghe; V. N. Seneviratne; Udayana Ranatunga; et al. (Scientific Reports, 2023)
Abstract The donor–acceptor (D-A) type of conjugated polymers has emerged as the paradigm of the third generation of electronically conducting polymers demonstrating improved infrared activity and intrinsic electronic conductivity. Judicious selection of donor (D) and acceptor (A) monomers for copolymerization can further fine-tune these properties. Notably, for such refinement, natural compounds provide many conjugated molecules with various functional groups. Berberine cation (Ber+) found in Coscinium fenestratum has extensive conjugation and contains both an electron deficient isoquinolium A moiety and electron-rich D-type methylenedioxy and methoxy groups. The incorporation of natural products in electronic materials is a novel area of research which opens a wide scope for future electronic and optoelectronic devices. Investigation of their fundamental properties via computer simulations is therefore important. In this study, quantum chemical calculations are performed using density functional theory (DFT) to investigate the electronic and optical properties of oligomers of Ber+ and 3,4-ethylenedioxythiophene (EDOT) and to explore the possibilities for homo-polymerization of Ber+ and its copolymerization with EDOT. It has been revealed that homo-polymerization is not favoured but copolymerization with EDOT is possible. As such, Ber+ was copolymerized with EDOT and the copolymers formed by electro-polymerization are extensively characterised and the D-A behaviour of the copolymers verified. Furthermore, the theoretical predictions have been compared with the experimental data.